2023
DOI: 10.1038/s41746-023-00756-4
|View full text |Cite
|
Sign up to set email alerts
|

Digital mental health for postpartum women: perils, pitfalls, and promise

Abstract: Postpartum mental health conditions are a public health concern, affecting a large number of reproductive-age women and their families. Postpartum depression alone affects at least 14% of new mothers and their families. However, very little has been written about how advances in digital mental health can benefit women in the postpartum period, or how those advances may poorly serve this vulnerable population. This manuscript takes a high-level view of the advances in different areas of digital mental health, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 32 publications
3
11
0
Order By: Relevance
“…A study from 2017 found a prevalence rate of over 50% that was significantly associated with maternal age, level of education and employment, monthly income, medical issues, unplanned pregnancy, and previous mental health issues [20]. We propose that the prevalence rate of PPD may be higher than detected in the studies reviewed, as many women may face these issues alone and do not report their struggles to healthcare providers due to societal expectations and concerns around the stigma associated with mental health issues [6,8,9,16,21].…”
Section: Introductionmentioning
confidence: 87%
See 4 more Smart Citations
“…A study from 2017 found a prevalence rate of over 50% that was significantly associated with maternal age, level of education and employment, monthly income, medical issues, unplanned pregnancy, and previous mental health issues [20]. We propose that the prevalence rate of PPD may be higher than detected in the studies reviewed, as many women may face these issues alone and do not report their struggles to healthcare providers due to societal expectations and concerns around the stigma associated with mental health issues [6,8,9,16,21].…”
Section: Introductionmentioning
confidence: 87%
“…The World Health Organization (WHO) prioritizes a healthy diet, that is, nutrition, weight management, physical activity, planned pregnancy, and physical, mental, and psychosocial health for women of reproductive age [1][2][3][4][5]. (Women's health issues are complex, and collaborative efforts are required to unravel some of these complexities in order to support women through their reproductive experiences, to enhance health and well-being, and to ensure better maternal outcomes [6][7][8][9]. Postpartum depression (PPD) is a common issue among childbearing women, as up to one in seven women will experience PPD [8,10,11].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations